Social Media Usage Among Agriculture Collegian in North-Eastern India - Pandey, D K; De, H K; Dubey, S K (Indian Journal of Extension Education, 2020)
The study attempts to understand the recent trends of social media use and the phenomenon of distractions among agriculture collegian in North-Eastern Hill states of India. A sample of 343 students drawn from 7 colleges of six North-Eastern Hill states was surveyed. The results showed rampant usage of social media among the agriculture collegians in the region. Social media like WhatsApp and Facebook were used by as many as 97 per cent and 93 per cent of the respondents respectively. Majority of the students spent significant amount of time on using social networking sites that too, regularly. Wastage of time in irrelevant activities and health related issues were perceived as major negative consequences of social media by the students. Social media exposure in higher agricultural education can play the positive role in information creation, sharing and socialization ultimately creating social wealth.